How Do Layoff Costs Affect Employment? - Lars Ljungqvist (Institute for the Study of Labor (IZA), 2001)
General equilibrium analyses of layoff costs have had mixed messages on the implications for employment. This paper brings out the economic forces at work and explains the disparate results. Specifically, we show that positive employment effects of layoff costs come through reducing labor reallocation, whereas negative effects come through reducing the private return to work due to those layoff costs and the associated inefficient allocation of labor. Additional adverse employment effects can arise through an increase in the effective bargaining strength of workers. These forces explain why layoff costs tend to increase employment in search models while the opposite is true in models with employment lotteries. In matching models, we show that the employment effects depend critically on how layoff costs are assumed to enter the bargaining process.
Keywords: E24; J63; J68; 330; Layoff costs; unemployment; Kündigung; Arbeitskosten; Beschäftigungseffekt; Theorie